Detection of pathogenic clostridia in biogas plant wastes - Neuhaus, Jürgen; Shehata, Awad A; Krüger, Monika (Folia microbiologica, 2015)
As the number of biogas plants has grown rapidly in the last decade, the amount of potentially contaminated wastes with pathogenic Clostridium spp. has increased as well. This study reports the results from examining 203 biogas plant wastes (BGWs). The following Clostridium spp. with different frequencies could be isolated via a new enrichment medium (Krüne medium) and detected by matrix-assisted laser desorption/ionization-time-of-flight mass spectrometry (MALDI-TOF MS): Clostridium perfringens (58 %) then Clostridium bifermentans (27 %), Clostridium tertium (23 %) and Clostridium butyricum (19 %), Clostridium cadaveris (15 %), Clostridium parapurificum (6 %), Clostridium glycolicum (5 %), Clostridium baratii (4 %), Clostridium sporogenes (2 %), Clostridium sordellii (1 %) and Clostridium subterminale (0.5 %). The mean most probable number (MPN) count of sulfite reducing bacteria was between 10(3) and 10(4)/mL, and the higher the MPN, the more pathogenic Clostridium spp. were present. Also, real-time PCR was used to be compared with culture method for C. perfringens, C. bifermentans, C. butyricum, C. sporogenes/Clostridium botulinum and C. sordellii. Although real-time PCR was more sensitive than the culture method, both systems improve the recovery rate but in different ways and are useful to determine pathogenic clostridia in biogas plants. In conclusion, BGWs could present a biohazard risk of clostridia for humans and animals.
Keywords: rostliny; Biofuels; Plants; Clostridium; odpadní produkty; biopaliva; Waste Products